Relationship between Nurse Communication and Nursing Documentation at Rizani-Paiton Hospital - Elvin Nur Avian, Moch.; Khotimah, Husnul; A.H, Maulidiyah Junnatul (Research of Service Administration Health and Sains Healthys, 2024)
Introduction: the importance of nurse communication in the hospital is the reason why nurses must be able to communicate effectively, therefore the National Hospital Accreditation Standard (SNARS) recommends a SBAR communication procedure which is expected to be a solution to the ineffectiveness of communication and to improve good nursing documentation based on communication which is also good among the medical team.Research objective: to determine the relationship between SBAR communication and nursing documentation at Rizani Paiton Hospital.Methods: This study used a quantitative descriptive approach using the Spearman's rho Correlation statistical test, with data collection instruments using a questionnaire. Research Results: Spearman's rho correlation test results obtained a P value of (0.000). Because the P value <0.05, H1 is accepted meaning that there is a significant relationship between SBAR communication and nursing documentation. Nurses' SBAR communication with nursing documentation had 104 nurses as respondents, while the results obtained in terms of SBAR communication with good SBAR communication categories were 94 nurses (90.4%), the SBAR communication category was sufficient for 10 nurses (9.6%) and . Meanwhile, in terms of nursing documentation, there were 99 nurses (95.2%) in the good category, and 5 in the sufficient category (4.8%).Conclusion: Good SBAR communication will also make good nursing documentation.